Semaglutide versus Tirzepatide - comparison of both drugs in treatment of diabetes type 2 and weight reduction - Staroń, Arkadiusz; Karkos, Patrycja; Kuśmierczyk, Katarzyna; Gastoł, Bartłomiej; Mikołap, Karolina; Kras, Marta; Jurga, Marta (Quality in Sport, 2024)
In recent years, the popularity of drugs which were firstly introduced as treatment for diabetes type 2 has surged, because of their’s significant effect of managing the body weight especially for patients that suffer for diabetes type 2. Tirzepatide is a dual glucose-dependent insulinotropic polypeptide and glucagon-like peptide-1 (GLP-1) receptor agonist. Semaglutide is a glucagon-like-peptide 1 receptor agonist. The aim of our study is to present reliable and up-to-date knowledge of effects that both drugs provide and their beneficial effects on health.